Chromatographic technique to support ADMET&DMPK in early drug discovery - Klara Livia Valko (International Association of Physical Chemists (IAPC), 2018)
The drug discovery process usually involves the discovery of a potent new chemical entity which has shown some activity on a target that is believed to be relevant in a certain type of disease. However, the structure and property of these putative drug molecules may have to be modified in order to ensure that they are able to exert the desired in vivo pharmacological effect. The candidate molecules usually have to be absorbed from the gastrointestinal system and therefore they must show appropriate solubility and permeability to be able to reach the target enzyme in vivo with a sufficient free biophase concentration at the site of action. This means that the physicochemical properties and the protein and phospholipid binding has to be optimized in order to achieve the desired in vivo ADMET and DMPK profile. The ADME studies usually require animal experiments or the use of biological samples, for example tissues which is expensive and involves time-consuming procedures. New technologies and approaches can accelerate this process.